Path Analysis: Factors Associated with Self Preventive Care among Patients with Type 2 Diabetes Mellitus in Surakarta - Ummy Prasetyowati; Didik Tamtoto; Bhisma Murti (Journal of Health Promotion and Behavior, 2018)
Background: